Processos de constituição e configuração de áreas públicas em cidades paulistas de porte médio: desafios para uma inserção urbana qualificada - Holanda, Lucas Padiá (Universidade Federal de São Carlos, 2021)
The constant expansion of urban space and its population increase has brought to light the issue of the importance of public spaces that promote the qualification of living conditions and full urbanity. In this sense, the objective of this research was to investigate the processes of constitution and configuration of public areas in six medium-sized cities in São Paulo, selected by the similarity of factors that will be addressed in the course of the work. They are: Araraquara, Araras, Limeira, Piracicaba, Rio Claro and São Carlos. The research method consisted in the survey, compilation, systematization and analysis of municipal legislation, in particular the Master Plans and the Land Division, Use and Occupation Laws for urban purposes. The analysis was based on a set of variables that included the percentages of public areas; their functional typologies; regulations relating to dimensioning proportionalities; physical-territorial configurations; requirements regarding their locations; and other specificities identified in each municipality. The obtained results pointed to a diversified legal repertoire in the ways of treatment of the adopted analysis variables, characterizing a panorama of some similarities and heterogeneities, expressing each municipal context. It is expected that this research, within a universe of analysis that included six medium-sized municipalities in São Paulo, and which sought to produce preliminary inputs for a critical and comprehensive view of this regulatory apparatus, will contribute to the qualification process of public areas arising from the processes of urban land subdivision.
Processes of constituition and configuration of public areas in medium-sized cities in São Paulo state: challenges for a qualified urban insertion
Keywords: Áreas públicas; Inserção urbana; Cidades médias; Parcelamento do solo urbano; Public areas; Urban insertion; Medium-sized cities; Urban land subdivision projects; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::FUNDAMENTOS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETO DO ESPACO URBANO